The contributing factors of large wildfires : exploring the main structural factors driving large wildfire ignition and spread in central Portugal (2005-2015) - Sousa, David Rodrigues Alves de (2019)
Dissertation presented as partial requirement for obtaining the Master’s degree in Statistics and Information Management, with a specialization in Information Analysis and Management